Multivariate analysis of vegetation of the salted Lower-Cheliff Plain, Algeria - Ababou, A.=700 1 Chouieb, M.; Khader, M.; Mederbal, K.; Saidi, D.; Bentayeb, Z.
(Es, En)
Ilus., 56 ref.
Keywords: PROPIEDADES FISICO-QUIMICAS SUELO; FACTORES EDAFICOS; DISTRIBUCION DE LA POBLACION; POBLACION VEGETAL; SALINIDAD; CARTOGRAFIA; MEXICO; SOCIEDAD BOTANICA DE MEXICO